Refinancing MFIs with market power: Theory and evidence - Lutz G. Arnold; Benedikt Booker; Gregor Dorfleitner; Michaela Röhe (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2016)
This paper presents a model of the complete microcredit financing chain investor -> MIV -> MFI -> micro-borrower, in which social-minded MIVs provide funds only to those MFIs which do not exploit their bargaining power towards micro-borrowers. The MFIs with the highest bargaining power do not use MIV capital, since eschewing their market power is most costly for them. Consistent with this prediction of the theoretical model, we find empirically that the net interest margin, as a measure of MFI market power, negatively affects the likelihood of using MIV finance. This lends support to the view that social criteria play an effective role in MIVs' investment policies, thereby also impacting MFIs' lending behavior.
Keywords: G21; 330; microfinance; microfinance investment vehicles; social returns